Application of People Tutor Methods to Increase Learning Achievement of Mechanical Measuring Equipment to Basic Automotive Engineering - Hengki Irawan (Universitas Sultan Ageng Tirtayasa, 2023)
The formulation of the problem in this classroom action research is how the application of the peer tutoring method can improve learning achievement in automotive engineering basic work subjects, basic competencies in applying mechanical measuring instruments and their functions. Subject of research students in class X Light Vehicle Engineering 1 SMK Negeri 1 Bulakamba, Brebes Regency, Semester Even the 2021/2022 Academic Year, The implementation of this classroom action research was carried out in two cycles. Technique of collecting data in this study were tests and questionnaires. Data analysis in this study was carried out in a quantitative descriptive manner. The results showed an increase in learning achievement in the initial conditions completed 55.56%, the first cycle conditions completed 80.97% and the second cycle conditions completed 94.40%.